Rhizoma coptidis as a Potential Treatment Agent for Type 2 Diabetes Mellitus and the Underlying Mechanisms: A Review - Ran, Qian; Wang, Jin; Wang, Lin; Zeng, Hai-rong; Yang, Xiang-bo; Huang, Qin-wan (Frontiers in Pharmacology, 2019)
Diabetes mellitus, especially type 2 diabetes mellitus (T2DM), has become a significant public health burden. Rhizoma coptidis (RC), known as huanglian, is widely used for treating diabetes in China. The bioactive compounds of RC, especially alkaloids have the potential to suppress T2DM-induced lesions, including diabetic vascular dysfunction, diabetic heart disease, diabetic hyperlipidemia, diabetic nephropathy, diabetic encephalopathy, diabetic osteopathy, diabetic enteropathy and diabetic retinopathy. This review summarizes the effects of RC and its bioactive compounds on T2DM and T2DM complications. Less research has been conducted on non-alkaloid fractions of RC, which may exert synergistic action with alkaloids. Moreover, we summarized the pharmacokinetic properties, structure-activity relationships of RC on T2DM with reference to extant literature and showed clearly that RC has potential therapeutic effect on T2DM.